2015
DOI: 10.1590/s0034-8910.2015049005953
|View full text |Cite
|
Sign up to set email alerts
|

Waiting time for radiotherapy in women with cervical cancer

Abstract: OBJECTIVE To describe the waiting time for radiotherapy for patients with cervical cancer.METHODS This descriptive study was conducted with 342 cervical cancer cases that were referred to primary radiotherapy, in the Baixada Fluminense region, RJ, Southeastern Brazil, from October 1995 to August 2010. The waiting time was calculated using the recommended 60-day deadline as a parameter to obtaining the first cancer treatment and considering the date at which the diagnosis was confirmed, the date of first oncolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
1
19
0
2
Order By: Relevance
“…Having a prevention and treatment program for over a decade was not enough to reduce the risk of death in the last five years of the 2000s or to reduce cervical cancer mortality rates. This reality points to problems in the PNCC that include low coverage of women aged 25-64 [14,[16][17], limited quality of collection, storage, and reading of slides [52,54], as well as difficulties in referral to the specialized care network in cases of precursor injury or cervical cancer [53][54]60].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having a prevention and treatment program for over a decade was not enough to reduce the risk of death in the last five years of the 2000s or to reduce cervical cancer mortality rates. This reality points to problems in the PNCC that include low coverage of women aged 25-64 [14,[16][17], limited quality of collection, storage, and reading of slides [52,54], as well as difficulties in referral to the specialized care network in cases of precursor injury or cervical cancer [53][54]60].…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that the PNCC be revised in order to reorient the practice of screening, moving to organized screening, especially in places with low spontaneous adherence and high coverage by primary health care. In addition, primary care physicians and nurses need to be trained in relation to PNCC guidelines regarding collection, storage, followup, and referral to the specialist network in situations where Pap tests show changes [53][54]60]. Associated with the measures described above, it is necessary that the states of Northeastern Brazil evaluate the referral and counter-referral process for the specialized cancer network, especially regarding: (i) time between referral and colposcopy;(ii) time between referral and biopsy; and (iii) the time between diagnosis of cervical cancer and initiation of treatment [66,67].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In middle and low income countries, the results are less expressive due to limitations of access to health services, low coverage of screening programs and delays in the implementation of diagnostic and therapeutic procedures. 4,5 With the objective of guaranteeing comprehensive care to individuals with a diagnosis of cancer, the Ministry of Health of Brazil, by means of decree GM/ MS No. 2,439, of 8 December 2005, established the National Policy of Oncology Care, emphasizing the importance of prevention, early diagnosis and timely treatment as measures to reduce the incidence and mortality from the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Among its therapeutic modalities, radiotherapy stands out, characterized by the emission of ionizing radiation aiming at curing, remission or control of physical symptoms and which can lead to adverse events that negatively impact the quality of life, increasing the care demand. [1][2] In this context, prolonged hospitalizations, interruption of treatment, clinical complications and dependence on care are common and affect both patients and family members who assume responsibilities as caregivers even without or with little technical-scientific preparation, representing a source support that seeks to promote health, prevent complications and provide rehabilitation. 3 Within this segment, family caregivers are considered to take care that requires availability and dedication without remuneration or professional training, such as the monitoring of disabilities and the management of physical symptoms and side effects resulting from treatment.…”
mentioning
confidence: 99%